Women Objectification in Carl's Jr TV Advertisements - Ivi Meiccel Vidia; Pratiwi Retnaningdyah (LPPM Universitas Bumigora Mataram, 2021)
The purpose of this paper is to explore the Indonesian youth audiences’ reaction to objectification in Carl’s Jr American TV ads. In the ads, white women become the focus of the ads and represent the product as a way to promote Carl’s Jr. The study aims at examining the representation of women in the ads from the audiences’ eyes and the audiences’ reaction to the objectification. Moreover, Frederickson & Robert's Objectification theory serves as the theoretical framework upon which women objectification is examined within the feminism and cultural contexts. The result of this study reveals that the audiences think the white women in the ads are being sexualized and objectified as the product that is being promoted. Furthermore, the audiences also think the women’s existences are reduced as a commodity to lure in male customers and increase the products’ sales. Some of the audiences think there is nothing wrong with the ads, some are neutral with it, while the rest wants the ads to be stopped.Keywords: Women objectification, audience reception.